2020
DOI: 10.1186/s40168-020-00923-9
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between host genetics and the gut microbiome reveals common and distinct microbiome features for complex human diseases

Abstract: Background Interest in the interplay between host genetics and the gut microbiome in complex human diseases is increasing, with prior evidence mainly being derived from animal models. In addition, the shared and distinct microbiome features among complex human diseases remain largely unclear. Results This analysis was based on a Chinese population with 1475 participants. We estimated the SNP-based heritability, which suggested that Desulfovibrionaceae and Odoribacter had significant heritability estimates (0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 88 publications
2
60
1
Order By: Relevance
“…There are many factors affecting microbiome-gut-brain-axis. These are diet, genetics, drugs, environment, exercise, cognitive behavior, stress, social interactions, and fear ( Figure 1 ) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Gut-brain-microbiota Axismentioning
confidence: 99%
“…There are many factors affecting microbiome-gut-brain-axis. These are diet, genetics, drugs, environment, exercise, cognitive behavior, stress, social interactions, and fear ( Figure 1 ) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Gut-brain-microbiota Axismentioning
confidence: 99%
“…It can possibly be used to treat and prevent osteoporosis by improving bone density through the production of vitamin K ( Fujita et al, 2012 ). In addition, low abundances of Bacteroides coprophilus in patients with multiple sclerosis and cardiac fibrillation ( Mirza et al, 2020 ; Xu et al, 2020 ) were reported in case-control studies. Indeed, the antibiotic diarrhea-prevention effects of Bacteroides fragilis ZY312 28 ( Zhang et al, 2018 ), anticancer and immune boosting effects of Bacteroides xylanisolvens DSM 23964 ( Ulsemer et al, 2016 ), and metabolic syndrome-related function of Bacteroides uniformis CECT7771 studied for use as probiotics ( Gauffin Cano et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Individual host genetics contribute a relatively minor portion of the variation within a person's microbiome, with lifestyle factors such as long-term diet substantially outweighing the contribution of any single nucleotide polymorphism (SNP) ( 4 ). Xu et al ( 5 ) calculated the heritability of α-diversity to be in a modest range of 3.5–10.3%; when they performed a genome-wide association study (GWAS) for enterotypes, no statistically significant signals were found. These results reflect a consensus that genetics’ impact on a person's microbiome composition is outweighed by lifestyle, geographical, and/or cultural factors ( 6 ).…”
Section: Host Genetics and Geographical Locationmentioning
confidence: 99%
“…However, this does not mean that host genetic variation is not a factor to consider when analyzing generally healthy individuals' microbiomes on the species level. For example, borrowing from the literature of microbiome-disease correlations where the data are plentiful, Mendelian randomization (MR) studies show that genetic predispositions to certain conditions such as chronic kidney disease have causal effects on specific bacterial species abundance ( 5 ). Such findings demonstrate the potential of leveraging large GWAS datasets such as the UK Biobank toward understanding similar host genome-microbiota dynamics in the generally healthy population.…”
Section: Host Genetics and Geographical Locationmentioning
confidence: 99%